GENETIC POLYMORPHISMS ASSOCIATED WITH HYPERTENSION IN THE ETHNIC POPULATIONS OF CALABAR AND UYO, NIGERIA (2012)
Hypertension is a public health challenge due to its high prevalence, and is a major risk factor for cardiovascular diseases. Hypertension is a complex disease resulting from an interaction of genes and environmental factors. Inconsistent association between polymorphisms of the renin angiotensin aldosterone, the atrial natriuretic peptide systems and hypertension has been reported among various ethnic groups, but not for the Efiks and Ibibios in south-south Nigeria. This study was designed to determine the frequency of gene polymorphisms of these two systems and their association with hypertension in Calabar and Uyo, Nigeria. A population-based case control design was used. A total of 1224 participants, 612 each of patients and controls were randomly recruited from hypertension clinics and the general population. Genotyping of the M235T allele of the angiotensinogen, Insertion/Deletion allele (I/D) of the angiotensinogen converting enzyme, A1166C allele of the angiotensin II type I receptor and C664G allele of the atrial natriuretic peptide genes to identify variants was performed using polymerase chain reaction and restriction enzyme digestion. The Hardy-Weinberg equation was used to calculate the allele and genotype frequencies. Plasma angiotensinogen levels were measured by Enzyme Linked Immunosorbent Assay. Hypertensinogenic factors such as age, familial history, physical exercise and drinking were assessed using questionnaires. Descriptive statistics, chi-square, multiple regression analysis and odds ratio were used to analyze the data. The frequency of the genotypes M235M, M235T, T235T of the M235T allele for the Efiks were 0.4, 7.7, 92 % in patients and 0, 6, 94 % in controls; for the Ibibios were 0.5, 1.2, 87 % in patients and 0, 7, 93 % in controls. The I/D genotypes II, ID, DD frequencies for the Efiks were 11, 44, 46 % in patients and 16, 45, 39 % in controls; for the Ibibios were 11, 40, 49 % in patients and 13, 49, 38 % in controls. The frequency of the A1166C carriers was 1 % while 99 % of the study population had the wild type A1166A genotype for the A1166C allele. Only the CC genotype was observed for the C664G allele. These frequencies did not conform to the Hardy-Weinberg assumptions. There were no significant differences between the genotype frequencies of patients and controls. Plasma angiotensinogen values were significantly higher in the patients with M235T allele than in the controls. Age was a positive predictor for systolic blood pressure (SBP, r = 0.60) in patients and diastolic blood pressure (DBP, r = 0.56) in controls. Other hypertensinogenic variables were not predictors for SBP and DBP in the population (p < 0.05). The Insertion/Deletion allele was a risk factor for hypertension, (O.R = 1.15). A high frequency was observed for the M235T allele and the Insertion/Deletion allele, which was associated with an increased risk for hypertension. The lack of association between the alleles of the M235T, A1166C and the C664G and hypertension suggests that other loci or environmental factors are involved in the disease outcome.